Manganese functionalized mesoporous molecular sieves Ti-HMS as a Fenton-like catalyst for dyes wastewater purification by advanced oxidation processes. Issue 4 (December 2016) - Song, Haiyan; You, Jiang-An; Chen, Chunxia; Zhang, Han; Ji, Xin Zhen; Li, Chunyu; Yang, Yi; Xu, Ningdi; Huang, Jie
Graphical abstract: Framework Ti gives promotion effect on Mn 2+ to generate more hydroxyl radicals for Fenton-like reactions, and the reactions of methylene blue (MB) and rhodamine B (RhB) take place in different sites on Ti-HMS. Highlights: Mn functionalized Ti-HMS molecular sieves were synthesized by in situ method. Mn 2+ was the main active site for Fenton reaction, and framework Ti gave a promotion effect. Mn/Ti-HMS obtained higher removal of MB and RhB in more moderate conditions than Fe/Ti-HMS. The spent Mn/Ti-HMS catalyst can be effectively regenerated by calcination. Abstract: Mn contained (Ti-)HMS catalysts were synthesized by in situ method using manganese acetate as Mn source. The samples were characterized by a series of techniques including XRD, N2 sorption, UV-vis, FT-IR and TEM, and their catalytic performance were tested in oxidative decolorization of methylene blue (MB) or rhodamine B (RhB) in model wastewater. Mn/Ti-HMS(50) as an optimized sample maintained highly ordered mesopores and uniform pore size distribution. Mn/Ti-HMS(50) obtained high removal and conversion of the dyes by using a small scale of H2 O2 via the Fenton-like process. In this bimetallic catalyst, Mn 2+ acted as the main active sites to generate most of the hydroxyl radicals for Fenton process, and the framework Ti gave an obvious promotion effect. A comparative study showed that Mn/Ti-HMS(50) obtained higher removal for MB, especially for RhB in more moderate conditions than Fe/Ti-HMS. Mn/Ti-HMS(50) was able to be reused for more than 3 times in decolorization of MB, but deactivated in decolorization of RhB. The spent catalyst can be effectively regenerated by calcination.